Cleopatra : the Story of the Beautiful Egyptian Queen. - Wilding, Valerie (Bloomsbury Pub., 2013)
Cleopatra is an iconic figure and one of the most powerful women in history. The last pharaoh of Egypt, and often depicted as a great beauty, she was renowned for her liaisons with the world's most powerful men, including Gaius Julius Caesar and Mark Antony. This fictional retelling of her life is a dramatic and thrilling story. Lives in Action is a series of narrative biographies that recount the lives of some of the key figures in history. Page-turning, thrilling plots that read like fiction will keep the most reluctant reader hooked.